Islamic banking adoption in Ghana - Abdul Razak, Dzuljastri; Abdul Wahab, Abdul Hamid (2019)
This study explores Islamic banking adoption in Ghana by examining the awareness, perceived importance and potential challenges of Islamic banking. It uses a qualitative research approach to gain insight about the perceptions of bank customers towards Islamic banking. A sample of eight respondents were interview. The findings suggested that awareness of Islamic banking is very low among Ghanaians though the perceived importance of Islamic banking is noteworthy. Furthermore, it discovers potential challenges of Islamic banking including competition with conventional banks and reluctance of non-Muslims to patronise Islamic banking.